THE IMPLEMENTATION OF THE GLOBAL MINIMUM TAX IN THEBULGARIAN LEGISLATION - Гьокче, Семра (E-Journal VFU, 2024)
The globalization and the digitalization of the economy turned out to be an enormous challenge when taxation multinational companies. Significant part of these companies found an alternative way for reducing their tax bases in their jurisdictions and shifting their profits to jurisdictions with no or low tax rates. From the end of 20thcentury, The Organization for Economic Co-operation and Development (OECD) is searching ways to reduce the negative effects from these actions for the revenues from corporate taxation and finally developed the Tax Challenges Arising from the Digitalisation of the Economy – Global Anti-Base Erosion Model Rules (Pillar Two) (‘OECD Model Rules’) approved on 14December 2021 by the OECD/G20 Inclusive Framework on BEPS. This agreement was accepted by 139 jurisdictions around the world. The countries within the European Union committed to be amongst the first countries to accept and implement the global tax reform till 31stof December 2023.The objective of this extensive reform is to limit the competition amongst the corporate tax rates by establishing a global minimum corporate tax rate. That framework creates a system of two interlocked rules, together referred to also as the ‘GloBE rules’, through which an additional amount of tax (a ‘top-up tax’) should be collected eachtime that the effective tax rate of an MNE in a given jurisdiction is below 15%.Bulgaria, being a member of the European union transposed in the national legislation the rules and principles of the DIRECTIVE (EU)2022/2523 of 14December 2022 on ensuring a global minimum level of taxation for multinational enterprise groups and large-scale domestic groups in the Union, by accepting the changes in the Corporate Income Tax Act in effect from 1stJanuary 2024. Unlike the rest of the European countries, the Bulgarian legislators adopted the rules for determining the national additional tax without taking full advantage of the substance -based income exclusion in full and de minimis exclusion provided for in the Directive. These issues are the subject of consideration in this article.
Keywords: globalization and digitalization; profit shifting; base erosion; exclusion; national additional tax; global corporate tax